2005
DOI: 10.17660/actahortic.2005.691.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leaf Area on Tomato Yield

Abstract: The influence of leaf area on tomato yield was evaluated, both by simulations and experimental work. Simulated crop growth results from daily crop gross assimilation rate minus maintenance respiration rate, multiplied by a conversion efficiency factor. Dry matter partitioning is simulated based on the relative sink strengths of the plant organs. Within the plant, individual fruit trusses and vegetative units are distinguished. Leaf area increase is calculated based on temperature, unless a maximum specific lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 11 publications
4
36
1
1
Order By: Relevance
“…These results agree with those reported in the literature, in the sense that the DM fraction for the leaves was higher (lower) than that for Bennett et al, 1979;Leskovar and Cantliffe, 1993;Wubs et al, 2007), tomato (69-74%; Heuvelink et al, 2005), cucumber (Cucumis sativus L.; 52-59%; Marcelis, 1993) and pepino (Solanum muricatum Ait. ; 30%; Fresquet et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with those reported in the literature, in the sense that the DM fraction for the leaves was higher (lower) than that for Bennett et al, 1979;Leskovar and Cantliffe, 1993;Wubs et al, 2007), tomato (69-74%; Heuvelink et al, 2005), cucumber (Cucumis sativus L.; 52-59%; Marcelis, 1993) and pepino (Solanum muricatum Ait. ; 30%; Fresquet et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…However, such an approach must also include considerations of how this will affect the crop yield. In studies, LAI has been shown to affect light interception and crop yield (Jones et al 1989, Heuvelink et al 2005. The amount of energy used for dehumidification could also be lower if the humidity set-point in a greenhouse is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a tomato crop in the Netherlands has a planting density of 2.5 plants m -2 and in summer stem density is 50% larger (3.75 stems m -2 ). Leaf picking strategy and the use of rootstocks may contribute to a higher LAI in summer (Heuvelink et al, 2005).…”
Section: New Trends In Crop Management Lai (Radiation Interception)mentioning
confidence: 99%